Expressing aspectual interactions in design: evaluating three AOM approaches in the slot machine domain - Fabry, Johan (2016)
In the context of an industrial project, we evaluated the implementation of the software of a casino slot machine. This software has a significant amount of crosscutting concerns that depend on and interact with each other as well as with the modular concerns. We therefore wished to express our design using an appropriate aspect-oriented modeling approach. We therefore evaluated three candidate methodologies: Theme/UML, WEAVR, and RAM to establish their suitability. Remarkably, only the last of the three has shown to allow an adequate expression of the interactions, albeit not fully explicit. The first two fall short because half of the interaction types cannot be expressed at all while the other half need to be expressed using a work-around that hides the intention of the design. Neither does RAM allow a fully explicit expression of interactions, but it would be the most adequate approach for the slot machine case.